Self Reported Dental Clinic Visits of Adolescents in Nigeria Rural Communities - Obehi O Osadolor (Update Dental College Journal)
Background: The health care utilization of a rural or urban population is dependent on their health seeking behaviour, which are activities carried out to maintain good health, to prevent poor health or any departure from a good state of health.